The Effect of Natural Disaster on Regional Economic Growth, Unemployment, Poverty, and Human Development Index in Thirty Indonesian Provinces - Aulia Puja Ilham; Sri Muljaningsih; Sasongko Sasongko (Department of Economics, Faculty of Economics and Business, Universitas Brawijaya, 2023)
Purpose The objective of this research is to identify the effects of natural disasters on several variables. The impacts were analyzed both directly and indirectly. Design/methodology/approach Using Partial Least Squares, natural disaster, regional economic growth, poverty, unemployment, and human development index as the variables with their own indicators. Findings This study finds that the direct effects of natural disasters are a significant reduction in regional economic growth, an insignificant increase in poverty, and a significant increase in unemployment. Furthermore, natural disaster have varying results in indirect effects. Research limitations/implications The limitation of this research is the use of natural disasters which only involves three types of natural disasters, as well as thirty provinces in Indonesia. Originality/value This study uses regional economic growth, unemployment, and poverty variables as intervening variables to determine the effect of natural disasters on the human development index which there are still not many similar studies on the disaster economics approach.